PREVENTION AND INFLUENCE OF ADVERSE RISK FACTORS FOR CARDIOVASCULAR DISEASES - Barno H. Abdullaeva; Durdona A. Raimova (Web of Journals Publishing, 2025)
Cardiovascular disease (CVD) is the leading cause of death worldwide, and people with or at high risk of CVD require early detection and care. Most cardiovascular diseases can be prevented by addressing risk factors such as unhealthy diet and obesity, physical inactivity, tobacco use, physical inactivity and harmful use of alcohol through population-based strategies.
Keywords: Cardiovascular morbidity, risk factors, coronary heart disease, primary health care, prevention.